O uso dos dons espirituais no livro de Atos - F. M. de Oliveira, Wanderson (Vox Scripturae - Revista Teológica Internacional, 2011)
This work seeks to make an exegesis of the Acts of the Apostles, seeking to find how the spiritual gifts were treated by the apostles and believers in the Primitive Church: if they were sought after, how they were discovered, used and the consequences of this use in the growth of the churches. In a general way, the motivation for the use of the spiritual gifts in modern churches has been focused on the aspect that the believers perform in church only the chores that are pleasant, presuming that his gifts will be available in this context, in doing in church what is pleasant or convenient.